Supply Chain Management Ubi Kayu (Manihot esculenta) di Agroindustri Tiwul Instan Kabupaten Gunungkidul - Maysaroh, Maysaroh; Irianto, Heru; Adi, Raden Kunto (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2018)
This research aims to know: supply chain management; supply chain management model; and supply chain performance of cassava in tiwul instan agroindustry, Gunungkidul Regency.  This research is a descriptive study. The location of the research is determine by purposive method. Data analysis method is descriptive using Food Supply Chain Network approach (Vorst) while the supply chain performance is measured by marketing margin and farmer?s share calculation. The result of this research shows that supply chain of cassava in tiwul instan agroindustry choose the domestic market as the target market while the development target of this supply chain is improvement in technology, coordination and collaboration, and the procurenment of formal contract agreement among the chain members. Cooperation is conducted by the basic of oral contract among the chain members, the transcation system is done in cash, and there has been government support such as capital aid, equipment, and training of human resource development. The management model of supply chain consist of farmer, collectors, market traders, and tiwul instan agroindustry as the chain members whom performing different activities depending on the input and the output. The most efficient channels is SC4 (farmer (gaplek) à market trader (gaplek) à tiwul instan agroindustry). SC4 is efficient because it has a relatively low marketing margin, relatively high farmer?s share and higher benefit and cost ratio than other channels.